Study of constitutional court decisions cancelling all norms in the law - Febriansyah Ramadhan; Ilham Dwi Rafiqi (Faculty of Law, University of Muhammadiyah Malang, 2021)
This article is the result of research on the heart article in the 3 Constitutional Court Decisions which canceled the entire contents of the law, namely the Constitutional Court Decision Number 001-021-022/PUU-I/2003 which canceled Law Number 20 of 2002 concerning Electricity, Constitutional Court Decision 006/PUU-IV/2006 which canceled Law 27 of 2004 concerning the Truth and Reconciliation Commission, Constitutional Court Decisions 11-14-21-126 and 136/PUU-VII/2009 which canceled the Law Number 9 of 2009 concerning Legal Education Entities, and the Constitutional Court Decision 85/PUU-XI/2013 which canceled Law Number 7 of 2004 concerning Water Resources. The term 'heart article' is the term coined by the Constitutional Court and used as the main reason for canceling the entire contents of the law. Unfortunately, in these decisions, the Constitutional Court did not elaborate further on the concept and characteristics of an article categorized as the heart article. Departing from this issue, this research aims to find out what are the concepts and characteristics of the